2020
DOI: 10.1096/fj.202001475r
|View full text |Cite
|
Sign up to set email alerts
|

High concentration of Cas12a effector tolerates more mismatches on ssDNA

Abstract: Rapid and sensitive pathogen detection cuts off routes of transmission and improves patient outcomes by enabling early treatment and appropriate antibiotic usage. 1 Several rapid methods having different adaptation, cost, sensitivity, and specificity, have been developed for pathogen detection. 2 Rapid pathogen detection, based on detection of nucleic acids via polymerase chain reaction (PCR), is often costly, requires specific equipment, and must be conducted in the laboratory environment. 3 Sequencing techno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 32 publications
1
14
0
Order By: Relevance
“…With regards to the analytical sensitivity of the CRISPR-Cas assays, the limit of detection (LoD) was evaluated in three types of concentration which include copies per mL, CFU per mL and molarity. For studies reporting the LoD in copies per mL, detection of Mycobacterium tuberculosis H37Rv utilizing EnGen LbaCas12a reported the lowest LoD of 1 copy/uL [ 40 ]. Meanwhile, most of the studies reported the LoD in CFU/mL, of which seven studies showed LoD of 1 CFU/mL.…”
Section: Resultsmentioning
confidence: 99%
“…With regards to the analytical sensitivity of the CRISPR-Cas assays, the limit of detection (LoD) was evaluated in three types of concentration which include copies per mL, CFU per mL and molarity. For studies reporting the LoD in copies per mL, detection of Mycobacterium tuberculosis H37Rv utilizing EnGen LbaCas12a reported the lowest LoD of 1 copy/uL [ 40 ]. Meanwhile, most of the studies reported the LoD in CFU/mL, of which seven studies showed LoD of 1 CFU/mL.…”
Section: Resultsmentioning
confidence: 99%
“…Compared to the previous study utilising ssDNA as a cas12a activator without PAM activation [13], the cas12a concentration of the AIOD-CRISPR system is 1.28µM due to buffer incompatibility of cas12a in RPA buffer, while for PECAN it is 0.2µM. Previous research investigating the specificity of cas12a detection of ssDNA template suggested that with higher cas12a enzyme in the reaction, the less specific the cas12a trans-cleavage activity is, as high concentrations of cas12a were shown to decrease the minimum activating bases for crRNA complementary sequence [35]. The high cas12a usage also leads to a detection cost per reaction of $5.4 USD.…”
Section: Discussionmentioning
confidence: 99%
“…However, it was shown that in ssDNA, a mismatch of the 5' end of crRNA could still lead to cas12a activation, leading to a minimum activation base of 11bp only in GC-rich crRNA, which is 3-bp shorter than using dsDNA. The same research group proposed some strategies; for example, using AT-rich crRNA target strand increases the specificity of ssDNA crRNA detection up to 14-bp minimum activation base [35]. This also suggests that the crRNA ssDNA hybridisation mechanism might be simple, like with the use of RPA fluorophore probe, which generates a free fluorophore per hybridised strand.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations